The combination of wheat peptides and fucoidan protects against chronic superficial gastritis and alters gut microbiota: a double-blinded, placebo-controlled study - Kan, Juntao; Cheng, Junrui; Xu, Leiming; Hood, Molly; Zhong, Dingfu; Cheng, Meijiao; Liu, Yumin; Chen, Liang; Du, Jun (European journal of nutrition, 2020)
Purpose Chronic gastritis is observed in almost half world population. Traditional medications against chronic gastritis might produce adverse effects, so alternative nutritional strategies are needed to prevent the aggravation of gastric mucosal damage. The aim of this study is to evaluate the protective effect of the combination of wheat peptides and fucoidan (WPF) on adults diagnosed with chronic superficial gastritis in a randomized, double-blind, placebo-controlled clinical trial. Methods Participants were randomized to receive WPF ( N = 53) or placebo ( N = 53) once daily for 45 days. Pathological grading of gastric mucosal damage was scored using gastroscopy. Fecal samples were collected for the determination of calprotectin, short chain fatty acids (SCFA) levels and metagenomics analysis. Questionnaires for self-reported gastrointestinal discomforts, life quality and food frequency were collected throughout the study. Results WPF intervention reduced gastric mucosal damage in 70% subjects ( P < 0.001). Significantly less stomach pain ( P < 0.001), belching ( P = 0.028), bloating ( P < 0.001), acid reflux ( P < 0.001), loss of appetite ( P = 0.021), increased food intake ( P = 0.020), and promoted life quality ( P = 0.014) were reported in the WPF group. WPF intervention significantly decreased fecal calprotectin level ( P = 0.003) while slightly increased fecal SCFAs level ( P = 0.092). In addition, we found altered microbiota composition post-intervention with increased Bifidobacterium pseudocatenulatum ( P = 0.032), Eubacterium siraeum ( P = 0.036), Bacteroides intestinalis ( P = 0.024) and decreased Prevotella copri ( P = 0.055). Conclusions WPF intervention could be utilized as a nutritional alternative to mitigate the progression of chronic gastritis. Furthermore, WPF played an important role in altering gut microbial profile and SCFA production, which might benefit the lower gastrointestinal tract.